The influence of lurah leadership on level of community participation in development in Sambau Village - Lestari, Linayati; Astria, Ika; Saputra, Praja Hadi; Muslihati, Atqiya; Ramelie, Norizan (2020)
The leadership of Lurah/ the Sambau Village head is democratic leadership seeing the leadership style applied ini the Sambau Village and together with the Sambau community, the village is part of the local government that provider population administration services directly to the community and development in the village. How the influence of the village head's leadership on the level of community participation in the development of the Sambau Village is a problem in this study. Knowing the extent of the influence of the village head's leadership on the level of community participation in the development of the Sambau Village and community participation in development in the Sambau Village. This research is expected to contribute knowledge, regarding the leadership of the village head to increase community participation in the development of Sambau Village. This research will describe related, autocratic, bureaucratic, diplomatic, participatory, and free. The type of research used in this research is descriptive type using a qualitative approach. Data collection used through field studies in the form of observation, interviews and documentation. The leadership of the village head of Sambau has exercised its role as an effective leader in the Kelurahan and has given the village staff the agreement to solve problems and the Sambau village head invites village staff to discuss policy making. The community participation of the Sambau sub-district has been better, by looking at community suggestions for development from the deliberation meeting of development planners at the village level.